Surface arcing of insulators due to bentonite contamination - Rusli, Halimatusaadiah; Gomes, Chandima; Kadir, Zainal; Abdul-Malek, Zulkurnain (Elsevier, 2015)
Impulse, alternating and direct voltage tests together with optical observations have been done under clean and polluted surface conditions with respect to bentonite, which is treated as a pollutant. The insulator materials tested were polymethyl methacrylate and polythene. Bentonite pollution may affect several surface flashover characteristics such as voltage at breakdown and 50% breakdown voltage under negative lightning impulse (1.2/50 μs) and the time to breakdown under wet condition for both negative and positive impulse voltage. There are four types of paths taken by the discharge channels, based on which the degree of degradation of the material surface may vary.